Cooling‐Accelerated Nanowire‐Nitinol Hybrid Muscle for Versatile Prosthetic Hand and Biomimetic Retractable Claw (Adv. Funct. Mater. 18/2022). (2nd May 2022) - Oh, Saewoong; Tabassian, Rassoul; Thangasamy, Pitchai; Mahato, Manmatha; Nguyen, Van Hiep; Nam, Sanghee; Huapeng, Zhang; Oh, Il‐Kwon
Abstract : Artificial Muscles In article number 2111145, Il‐Kwon Oh and co‐workers grow a copper nanowire forest directly on the surface of a shape memory alloy coil (SMAc) to provoke thermal dissipation and accelerate its actuation speed. Then, the cooling‐accelerated Cu nanowire grown SMAc is applied as artificial muscles for a versatile prosthetic hand capable of making a series of sign languages and playing the grand piano. Moreover, a unique feature of felines, a retractable claw, is realized by using the cooling‐accelerated Cu nanowire grown SMAc for successful control of traction force.